(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with determination of conditions of such a constituent in the sphere of hospitality as catering establishments in Mykolayiv during the last third of ХІХ ñ the beginning of ХХ century, analyzing its structure, quantitative and tendencies of its development.